The psychophysiological determinants of pacing during prolonged endurance exercise: Performance level comparison - Venhorst, A.; Micklewright, D.; Noakes, T. D. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The Central Governor Model (CGM) revolutionized our current understanding of fatigue and ignited a paradigm shift in the exercise sciences from catastrophic failure towards central regulation. However, the CGM and alternative psychobiological models rely heavily on the Gestalt measurement of perceived exertion to explain behavioral change. This is an oversimplification of the underlying psychophysiological construct. Drawing from Gate Control Theory of pain, a modified three-dimensional model of effort was applied to explore the distinct inputs that shape the perceptual milieu and underpin the goal directed behavior of pacing. Methods: Delineated contributions of the sensory-discriminatory, affective-motivational, and cognitive-evaluative dimensions were approximated by means of scales: physical-rating of perceived exertion (p-RPE) and mental sense of effort (TEA), affective valence (FS) and felt arousal (FAS), and perceived action crisis (ACRISS), respectively. Cyclists of different performance levels (PL3, n=12 and PL4, n=11) performed a 70 km individual time trial over a virtual profiled course. The interrelationships between pacing strategy, performance, hematological, and perceptive variables were explored. Results: PL4 performed at greater workloads (p=0.015) and higher relative intensities (p=0.042) compared to PL3, and had greater blood norepinephrine (p=0.045) and lactate levels (p=0.039). Despite greater physiologic strain, PL4 felt more pleasure (p=0.045) and better maintained hedonic tone and arousal levels (p=0.022), which deteriorated in PL3 over the last third of the course. FAS correlated with all markers of cardiovascular fitness and performance (p<0.05). Split times were faster in PL4 except during the downhills (p=0.001), which coincided with lower p-RPE (p=0.018) compared to PL3. p-RPE correlated with dynamic change in cortisol (p<0.01). Discussion: The current data revealed differences in pacing strategies between performance levels and indicate that perceptions of peripheral strain (approximated by p-RPE) were closer related to dynamic changes in pace than perceptions of mental strain (approximated by TEA). Data also showed a performance level dependent relationship between core affect and performance providing evidence for the important role of affective states in the regulation of exercise behavior. Well-trained cyclists paced themselves in a way that prevented the development of an action crisis, suggestive of performance level dependent differences in the integration and interpretation of perceptual sensory and affective cues. The proposed model provides additional and differential information on the complex processes underpinning exercise behavior.